Establishment of control standard for plastic deformation performance of graded crushed stone. (30th June 2019) - Xu, Gui; Chen, Zhongda; Li, Xiaodong; Lu, Guanghui; Dong, Dingming; Liu, Zixi
Highlights: PDI was proposed as evaluation indicator of plastic deformation performance of GCS. Typical asphalt pavements with GCS base were selected as analytical objects. The critical plastic deformation of GCS base at failure was calculated. Plastic deformation of GCS base at a given time was calculated. Requirement for PDI values of different highway grades were determined. Abstract: Plastic deformation of graded crushed stone (GCS) exceeding a certain threshold is prone to cause the failure of GCS base and the excessive deformation of asphalt pavement. However, few studies have been conducted regarding a control standard of the plastic deformation performance of GCS. This study attempted to establish the control standard by setting a threshold of an evaluation indicator. The plastic deformation index (PDI) was proposed as the evaluation indicator. The plastic deformation of GCS base at failure was obtained on the basis of the typical asphalt pavements with GCS base and a failure criterion with 4% plastic strain. The plastic deformation of GCS base at a given time (i.e., corresponding to the number of load repetitions) was further calculated based on the stress condition of GCS base and a prediction model for the plastic deformation of GCS base. The requirement for PDI values of different highway grades were determined by the calculation equation of PDI, and the control standard was ultimately established. The results showed that: the PDI value should be less than or equal to 1900 mm· number for expressway and first-grade highway; the PDI value should be less than or equal to 2200 mm· number for secondary road.